Avaliação funcional de mutações no gene da tireoperoxidase identificadas em pacientes com hipotireoidismo congenito por disormonogênese - Silva, Marlon Messias da Conceicao [UNIFESP] (2016)
Congenital hypothyroidism (CH) is the most common cause of mental retardation that can be prevented with early treatment, with frequency of 1/2500 birth. CH can be caused by defects in the development of thyroid (dysgenesis) or by defects in the thyroid hormone synthesis (dyshormonogenesis). The most frequent mutations associated with the dyshormonogenesis are located in the thyroid peroxidase gene (TPO). These mutations can promote the substitution, deletion or addition of amino acids resulting in the reduction of enzymatic activity by structural changes of the protein and/or impair localization in the thyrocyte. The objective of this project was to carry out the functional study of the TPO mutations p.Gly319Glu, p. Ala909Thr; Ala911fs*49, p.Gln660Glu and p.Cys296Alafs* 21 previously identified in Brazilian patients with congenital hypothyroidism due to dyshormonogenesis with partial iodine organification defect or fetal goiter. In the functional analysis the plasmid containing the wild TPO gene was used and the mutations were introduced by site directed mutagenesis. The proteins were expressed in mammalian cells HEK 293 transiently transfected using lipofectamine and cotransfected with pmaxGFP to determine the technical efficiency. After 72 hours of transfections, it was evaluated the enzymatic activity of TPO using the Amplex Red kit (Invitrogen, Carlsbad, CA USA), the size of the expressed proteins by western blot and cellular localization by immunofluorescence microscopy, always comparing the results of the mutants TPO with the wild-type. Enzymatic analysis showed reduced extracellular activity of all mutants TPO compared to wild type (p <0.05). It was observed that mutations p.Gly319Glu, p.Gln660Glu p. Ala909Thr;Ala911fs*49, e p.Cys296Alafs*21 promoted a reduction of activity of 35,3%, 38,7%, 44,30% and 49,2% of the wild type TPO, respectively. The western blot experiments showed that the proteins p.Gly319Glu and p.Gln660Glu have similar molecular size to the wild type, 103 kDa protein, the TPO p.Ala909Thr;Ala911fs*49 approximately 108 kDa due to the incorporation of 49 amino acids and the TPO p.Cys296Alafs*21 has 35 kDa, confirming to be a truncated protein in the exon 8. The Immunofluorescence results showed that all mutated TPO were expressed in HEK293 cells however, with the exception of p.Gln660Glu, all mutated TPO showed lower membrana immunostaining as compared to the wild type. We conclude therefore that the TPO alterations caused by the studied mutations reduce the catalytic capacity of the enzyme and/or its correct localization in the plasma membrane. These data may explain the CH due to thyroid hormone synthesis defect observed in the patients with these mutations. Furthermore, the intermediate enzymatic activity of TPO and the reduce presence of mutants TPO (p.Gly319Glu and p.Gln660Glu, p.Ala909Thr;Ala911fs*49) in the plasma membrane is in agreement with the less severe HC phenotype of the patients confirmed by the partial iodine organification defect. More studies are needed to understand the presence of fetal goiter in patients with p.Cys296Alafs*21 that may be associated to a very severe defect in thyroid hormone synthesis.